2021
DOI: 10.1039/d0ma01027h
|View full text |Cite
|
Sign up to set email alerts
|

An ultrathin and compact electron transport layer made from novel water-dispersed Fe3O4 nanoparticles to accomplish UV-stable perovskite solar cells

Abstract: UV induced decomposition of perovskite material is one of main factors to severely destroy perovskite solar cells for instability. Here we report a UV stable perovskite solar cell with a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Perovskite-based solar cell devices generally consist of a perovskite layer, an electron transporting layer (ETL), a hole transporting layer (HTL), anode and cathode layers, as depicted in Figure (f) . Iron oxides are reported previously compatible with perovskite-based PV devices as an electron transport layer and other complementary layers that can significantly impact the PCE of the perovskite-based solar cells. , …”
Section: Recent Photovoltaic Technologiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Perovskite-based solar cell devices generally consist of a perovskite layer, an electron transporting layer (ETL), a hole transporting layer (HTL), anode and cathode layers, as depicted in Figure (f) . Iron oxides are reported previously compatible with perovskite-based PV devices as an electron transport layer and other complementary layers that can significantly impact the PCE of the perovskite-based solar cells. , …”
Section: Recent Photovoltaic Technologiesmentioning
confidence: 93%
“…73 Iron oxides are reported previously compatible with perovskitebased PV devices as an electron transport layer and other complementary layers that can significantly impact the PCE of the perovskite-based solar cells. 74,75 2.5.3. Polymer.…”
Section: Dye-sanitized Solar Cells (Dsscs)mentioning
confidence: 99%
“…tin dioxide (SnO 2 ) [65,105,127,128] and zinc oxide (ZnO) [21,105], are the widely used inorganic ETLs this far. Other materials such as Fe 2 O 3 [129],…”
Section: Perovskite Surfacesmentioning
confidence: 99%
“…Perovskite solar cells, a new class of solar cells, have drawn extensive attention and shown good application prospects so far. It takes about a decade to achieve improvements in its efficiency from 3.8% to higher than 25.5%, which is comparable to that of silicon solar cells. To the best of our knowledge, most of the perovskite solar cells are made up of five functional layers: conductive glass, electron transport layer (ETL), perovskite layer, hole transport layer (HTL), and metal electrode. A well-functional ETL generally has a high ability of charge transfer performance. , Tin oxide (SnO 2 ) is considered a quite good ETL material because of its high charge transfer ability, chemical stability, nontoxicity, and cheap price. Seo et al reported that the SnO 2 ETL exhibited the best electrical properties after fine-tuning the SnO 2 growth process at different reaction times . The photoelectric conversion efficiency (PCE) of the cell prepared by the modified ETL can reach 80.5% of the thermodynamic limit value.…”
Section: Introductionmentioning
confidence: 99%